Current and upcoming anti-VEGF therapies and dosing strategies for the treatment of neovascular AMD: a comparative review. Issue 1 (15th December 2019) - Khanna, Saira; Komati, Rahul; Eichenbaum, David A; Hariprasad, Ishani; Ciulla, Thomas A; Hariprasad, Seenu M
Abstract : Age-related macular degeneration is the leading cause of vision loss in the developed world, with the expected number of affected elderly individuals reaching 17.8 million. Antivascular endothelial growth factor (anti-VEGF) injection therapy has been instrumental in treating a disease process that was previously thought to be untreatable. Over the past two decades, landmark studies have demonstrated the efficacy of different anti-VEGF medications and investigated the optimal dosing regimen and delivery mechanism to increase overall vision and minimise patient burden. In this review, we outline landmark neovascular age-related macular degeneration clinical trials that have demonstrated level 1 evidence for its usage or have contributed to the understanding of how to dose these agents.